2018
DOI: 10.1007/s10597-018-0348-3
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Service Use and Perceived Unmet Needs for Mental Health Care in Asian Americans

Abstract: Using data from the Asian American Quality of Life (AAQoL, n = 2609) survey, logistic regression models of mental health service use and perceived unmet needs were estimated with background variables, ethnicity, and mental health status. More than 44% of the participants were categorized as having mental distress (Kessler 6 [K6] ≥ 6) and 6.1% as having serious mental illness (SMI, K6 ≥ 13). About 23% had used services (mental health specialist, general doctor, and/or religious leader) for their emotional conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 17 publications
3
16
0
Order By: Relevance
“…The Korean sample showed higher scores on functional disability and depressive symptoms, and their self-rated health was more positive than that of the Chinese sample. The high levels of depressive symptoms observed in older Korean Americans are consistent with literature reporting mental health vulnerabilities of the Korean American population in general and its older members in particular [ 20 , 32 , 33 ].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The Korean sample showed higher scores on functional disability and depressive symptoms, and their self-rated health was more positive than that of the Chinese sample. The high levels of depressive symptoms observed in older Korean Americans are consistent with literature reporting mental health vulnerabilities of the Korean American population in general and its older members in particular [ 20 , 32 , 33 ].…”
Section: Discussionsupporting
confidence: 89%
“…Responding to the dearth of data on older Asian Americans and the persistent challenges in reaching out to them [17][18][19][20], we harmonized two sets of data from older Chinese and Korean Americans (PINE and SOKA), which were independently collected using culturally and linguistically sensitive approaches. With a combined sample size of 5,063, the harmonized data demonstrated similarities and differences in physical and mental health between older Chinese and Korean Americans and provided support for our hypothesized mediation model of selfrated health.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despites such data, the literature notes that Asian Americans have low mental health service utilization despite existing need. For example, using the Asian American Quality of Life survey, Jang et al [2] noted that while 44% of participants had mental distress, only 23% reported any mental health service utilization. Likewise, in summarizing existing literature, Tung [3] noted that only 8.6% of the Asian American population used any mental health related service, as compared to nearly 18% of the general U.S. population.…”
Section: Introductionmentioning
confidence: 99%